Association between Forced Expiratory Volume in 1 second /Forced Vital Capacity ratio and Main Pulmonary Artery /Ascending Aorta ratio in Chronic Obstructive Pulmonary Disease Patients – A Hospital based Observational Study - Sindhu, Naru Sai; L, Muthukumaran; S, Chandrasekar; Natarajan, Sekar; R, Sridhar; N, Meenakshi (Journal of Neonatal Surgery, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a condition marked by persistent airflow limitation with an enhanced inflammatory response in airways and alveoli. Key risk factors for COPD include smoking, exposure to environmental pollutants, and genetic predisposition. Low dose computed tomography (LDCT) chest offers valuable insights into structural and vascular abnormalities in COPD, contributing to better understanding of its phenotypes, severity and disease outcomes. Objective: This study aims to evaluate the correlation between disease severity (FEV1/FVC) and MPA/AA ratio in LDCT chest. Methods: This observational study included a total of 112 spirometry confirmed COPD patients. LDCT chest was performed to assess parenchymal abnormalities and vascular involvement. Statistical analyses were conducted to determine the significant association between disease severity (FEV1/FVC) ratio, MPA/AA ratio and frequency of exacerbations over one year. Results: Patients with very severe and severe COPD disease exhibited elevated MPA/AA ratio and reduced FEV1/FVC ratio, with a significant negative correlation between FEV1/FVC and MPA/AA (r = -0.533, p = 0.001). A strong association was observed between increased MPA/AA ratio (>0.9) and higher risk of exacerbations (p < 0.001, OR = 2.42, 95% CI: 4.811–15.365). The most common parenchymal abnormality detected on LDCT chest was mosaic attenuation, observed in 38 patients. Conclusion: This study focuses the utility of LDCT chest in COPD patients. The strong correlation between FEV1/FVC ratio, MPA/AA ratio and exacerbation frequency emphasises the disease severity in COPD patients, thus facilitating targeted interventions to improve disease condition.